Refractive, biometric and corneal topographic parameter changes during 12 months of orthokeratology - Queirós, A. (2020)
Background The aim of this study was to monitor refractive, topographic and biometric changes in Singaporean myopic children fitted with orthokeratology over a period of 12 months. Methods Data from 62 myopic eyes from an Asian population corrected with orthokeratology were retrospectively collected from an optometric clinic in Singapore. Anterior segment parameters were analysed with a Pentacam. Axial length was measured using the IOLMaster and refraction was assessed by subjective examination before the treatment and after one night, one week, and one, three, six and 12 months. A logistic regression model was built to evaluate the probability of slower (< 0.10 mm/year) or faster eye growth (>= 0.10 mm/year). Results Subjects had a mean age of 12.2 +/- 3.9 years (range 5-19 years), and 71 per cent were female. Baseline myopia was -3.95 +/- 1.59 D (range -1.50 and -8.75 D). Statistically significant differences were found after 12 months of treatment for refractive error, parameters of the central anterior corneal surface (curvature and elevation) and central corneal thickness. Topographic and thickness changes stabilised after one week of treatment. During 12 months of orthokeratology treatment there was a significant increase of axial length (difference = 0.11 +/- 0.18 mm, p < 0.001) while refraction remained stable. Changes in axial length of subjects above 11 years were not statistically significantly independent of the baseline myopia, and in subjects with baseline myopia greater than 4.00 D. Logistic regression showed that each additional year of age and each additional dioptre of baseline myopia decreased the probability of faster axial elongation (odds ratio [OR] = 1.23, 2.19 95% CI; OR = 1.08, 3.47 95% CI, respectively). Conclusion Corneal parameters in orthokeratology treatment were stable after one week, particularly for myopes under 4.00 D. Axial length did not change significantly in children older than 11 years of age or in subjects with myopia above 4.00 D undergoing orthokeratology treatment.